Illumina Based Analysis of Bacterial and Fungal Flora in Foreguts and Hindguts of Crucian Carp (Carassius Aumtus) in Retail Markets - Mingyue Wang; Miaomiao Yin; Hongming Tan; Lixiang Cao (Open Journal of Bacteriology - Peertechz Publications, 2017)
The intestinal microbiota of fish are the major cause for spoilage. To elucidate the bacterial and fungal community of guts, the bacterial and fungal taxa in foreguts and hindguts of crucian carp (Carassius aumtus) were analyzed by Illumina-based sequencing. Results suggested that the foreguts contained more diverse bacteria than those in hindguts; nevertheless, the hindguts contained more diverse fungi than foreguts. The anaerobic bacterial genera Cetobacteri Desulfovibrio and Shewanella in foreguts were still detected in hindguts. The fungal taxa in foreguts were different from those in hindguts. The dominant fungal genera Alternaia (78.6%), Massarina (0.8%) and Fusarium (0.2%) were only detected in hindguts. It was considered that the Alternaria, Emericella, and Cochliobolus might derive from the diets of     crucian carp. The activities of Desulfovibrio might be responsible for the changes in odour, flavor and texture of the fish meat. The H2S produced by Desulfovibrio is potentially a major toxin to the fish gut epithelium and promoted the fi sh spoilage processes. The results are helpful for manipulation of intestinal flora to preserve fresh crucian carp in tanks.